Ergonomisk och rationell montering av ramlageröverfall: Ergonomiförbättringar på Volvo GTO i Skövde - Karlsson, Simon (My University, 2023)
The following report is the result of our work that has been carried out on behalf of and in collaboration with Volvo Group Trucks Operations in Skövde, Sweden. The thesis work aims to improve the physical ergonomics of a workstation in their production line. Physical ergonomics involves, for instance, how loads in work affect the body and is an important factor to take into consideration during improvement work to minimize the risk of work related injuries. Volvo has noticed that this specific workstation needs an ergonomic improvement. The work is based on the following question: - In which different ways is it possible to improve the physical ergonomics of the workstation? To find suitable solutions, a current state situation analysis has been carried out. The current situation analysis made it clear that the workstation required an ergonomic improvement. Later on, a requirements specification was made, based on the current state analysis together with the requirements and wishes of Volvo. This requirements specification was taken into consideration during the development of concepts and later on in the evaluation of the concepts. The concepts that were developed were divided into concept groups, where two of the groups were left after the evaluation and elimination. These two concept groups include a form of lifting tool and extended intermediate storage. After evaluating the concepts, an electric lifting tool for the assembly of the main bearing caps and a magnetic lifting tool for the material handling were chosen as the most suited solution to this ergonomic issue
Keywords: ergonomi, fysisk ergonomi, förbättringsarbete, manuellt arbete, lyftverktyg